Addressing Health Literacy as a Foundation for Effective and Equitable Health Communication. Issue 2 (3rd April 2021) - Caballero, Alison
Abstract: Health behaviors contribute heavily to health outcomes and play a role in health disparities. To develop health education programming that is equitably accessible, health communicators in clinical and public health settings will be optimally positioned for success when they use a combination of strategies in the development and implementation of programming. Those strategies include use of health behavior theory to select content, plain language communication techniques to address limited health literacy, and a dissemination strategy designed to reach those who need information most but are often difficult to reach.